2002
DOI: 10.1111/j.1524-6175.2002.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

How Relevant and Frequent Is the Presence of Mild Renal Insufficiency in Essential Hypertension?

Abstract: Recent analyses of the influence of renal function on the cardiovascular outcome in essential hypertensive patients have confirmed the relevance of the kidney in cardiovascular prognosis even in the initial stages of renal failure. The evaluation of renal function in clinical practice is based mainly on the finding of changes in serum creatinine, but the estimation of creatinine clearance or its determination after 24-hour urine collection is not usually performed. The objective of this study was to analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 20 publications
0
28
0
5
Order By: Relevance
“…Age ≥ 65 years presented a significant association with reduced GF in both groups at the non-adjusted analysis and so it remained after the adjustment. National 10,20 and international studies 4,19 also observed a statistical significance of reduced GF with age. These findings confirm the increase in AP and CKD with age.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Age ≥ 65 years presented a significant association with reduced GF in both groups at the non-adjusted analysis and so it remained after the adjustment. National 10,20 and international studies 4,19 also observed a statistical significance of reduced GF with age. These findings confirm the increase in AP and CKD with age.…”
Section: Discussionmentioning
confidence: 85%
“…However, these formulas, although recommended, still need validation in large samples, in individuals at very early stages of kidney dysfunction and in elderly individuals 35,36 . Microalbuminuria significantly increases with the reduced GF 4 . Therefore, its measurement constitutes an important element in the early diagnosis and follow-up of CKD 9,30 .…”
Section: Discussionmentioning
confidence: 93%
“…The Heart Outcomes Prevention Evaluation (HOPE) study showed a prevalence of CKD of 10.4% according to serum creatinine values Ͼ 1.4 mg/dl (21). We have recently described that 7.6% of patients referred to our hypertension unit have a decreased renal function according to serum creatinine levels, and one of every four patients has a decreased creatinine clearance (12). The prevalence of CKD in the community could be even higher according to the values of estimated creatinine clearance seen in the Third National Health and Nutrition Examination Survey (NHANES III) (7,22).…”
Section: Discussionmentioning
confidence: 99%
“…In 500 untreated hypertensive patients followed until death, Perera (20) described that proteinuria was present in 42% and chronic renal failure in 18%. Growing evidence indicates that renal prognosis is not so good in either hypertensive patients or the general population (4,(7)(8)(9)(10)(11)(12). The Heart Outcomes Prevention Evaluation (HOPE) study showed a prevalence of CKD of 10.4% according to serum creatinine values Ͼ 1.4 mg/dl (21).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that even minor degrees of renal dysfunction were associated with an enhanced cardiovascular (CV) risk [2,3]. Among hypertensive patients, CKD is much more prevalent [4,5,6] and is a risk factor for CV events and all-cause mortality [7,8,9]. Guidelines for the management of hypertension have recognized the relevance of albuminuria and decreased estimated glomerular filtration rate (eGFR) on CV prognosis in hypertensive patients [10,11].…”
Section: Introductionmentioning
confidence: 99%